2016
DOI: 10.1177/1069072716639852
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Validation of the Career Calling Scale for Korean Emerging Adults

Abstract: This study set to provide an age- and culturally-appropriate measure of career calling for Korean young adults. We conducted a literature review and identified a suitable, 15-item Career Calling Scale for Emerging Adults. We translated all items into Korean, back-translated into English, and verified for accuracy. An exploratory factor analysis revealed three factors reflecting those of the original scale ( other-oriented meaning, active engagement, and personal meaning; Stage 1; N = 152), and a confirmatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Although some scholars have divided career calling based on the specific performance, different status and motivation (Dobrow and Tosti-Kharas, 2011; Dik et al , 2012; Duffy et al , 2012; Hagmaier and Abele, 2012), they neglect the classification based on the meaning of employees’ career calling. Moreover, while previous research studies on career calls have focused on the western culture that advocates freedom and self-protection, the oriental culture that advocates collectivism has received scarce attention (Praskova et al , 2015; Kim et al , 2017; Zhang et al , 2015a; Zhang et al , 2015b). Meanwhile, existing research studies in the context of oriental culture are mainly concern about college students instead of colleagues (Zhang et al , 2015a; Zhang et al , 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Although some scholars have divided career calling based on the specific performance, different status and motivation (Dobrow and Tosti-Kharas, 2011; Dik et al , 2012; Duffy et al , 2012; Hagmaier and Abele, 2012), they neglect the classification based on the meaning of employees’ career calling. Moreover, while previous research studies on career calls have focused on the western culture that advocates freedom and self-protection, the oriental culture that advocates collectivism has received scarce attention (Praskova et al , 2015; Kim et al , 2017; Zhang et al , 2015a; Zhang et al , 2015b). Meanwhile, existing research studies in the context of oriental culture are mainly concern about college students instead of colleagues (Zhang et al , 2015a; Zhang et al , 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Most research that has examined work-related outcomes of living a calling has assessed job satisfaction. With general samples of working adults (Chen, May, Schwoerer, & Augelli, 2016; Duffy et al, 2012, 2014) and adults representing diverse identities (e.g., in terms of lesbian/gay/bisexual/transsexual/queer status and country of origin; Allan, Tebbe, Duffy, & Autin, 2015; Douglass et al, 2016; Kim, Praskova, & Lee, 2016; Lazar, Davidovitch, & Coren, 2016; Xie, Xia, Xin, & Zhou, 2016), studies have found living a calling to strongly relate to job satisfaction. Therefore, we hypothesize that living a calling predicts satisfaction with one’s job (Proposition 20).…”
Section: Outcomes Of Living a Callingmentioning
confidence: 99%
“…Their specific recommendation is based on the comparative cultural assumption that the model may need to be modified for different cultural contexts. Some research already indicates that the core elements of the WCT model apply to diverse cultural contexts (Douglass et al, 2016; Hirschi, 2012; H. J. Kim et al, 2016; Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%